Evaluation of Long Term Effect of RV Apical Pacing on Global LV Function by Echocardiography - Sarkar, Narayan Chandra (J Clin Diagn Res, 2016)
INTRODUCTION: We very often face pacemaker implanted patients during follow-up with shortness of breath and effort intolerance inspite of normal clinical parameters. AIM: The aim of our study is to evaluate the cause of effort intolerance and probable cause of sub-clinical Congestive Cardiac Failure (CCF) in a case of long term Right Ventricular (RV) apical pacing on global Left Ventricular (LV) function non- invasively by echocardiography. MATERIALS AND METHODS: We studied 54 patients (Male 42, Female 12) of complete heart block (CHB) with RV apical pacing (40 VVI and 14 DCP). Mean duration of pacing was 58+4 months. All patients underwent 24 hours Holter monitoring to determine the percentage of ventricular pacing beats. 2-D Echocardiography was done to assess the regional wall motion of abnormality and global LV ejection fraction by modified Simpson’s rule. These methods were coupled with the Doppler derived Myocardial Performance Index (MPI), tissue Doppler imaging, and mechanical regional dyssynchrony with 3-D Echocardiography. Data were analysed from 54 RV- apical paced patients and compared with age and body surface area of 60 controlled subjects (Male 46, Female 14). RESULTS: Evaluation of LV function in 54 patients demonstrated regional wall motion abnormality and Doppler study revealed both LV systolic and diastolic dysfunction compare with control subjects (regional wall motion abnormality 80±6% vs 30±3% with p-value<0.0001) which is proportional to the percentage of ventricular pacing beats (mean paced beat 78%). Global LVEF 50±4% vs 60±2% (p-valve <0.0001) and MPI 0.46 ±0.12 v/s 0.36±0.09 (p-value <0.0001). CONCLUSION: RV–apical pacing induces iatrogenic electrical dyssynchrony which leads to remodeling of LV and produces mechanical dyssynchrony which is responsible for LV dysfunction. Alternate site of RV pacing and/or biventricular pacing should be done to maintain biventricular electrical synchrony which will preserve the LV function.